Eddy current damping applications for vibration isolation purposes - Özkaya, Efe. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this thesis, passive eddy current damping (ECD) is used in two di erent novel designs that show vibration stop bands. One includes an inertial ampli cation mechanism and the other includes local resonators. In both designs, copper tube-ring magnet couple is used as a passive eddy current damper. The reason for such usage arises from the fact that this damping method does not require an external power source and its damping constant can be easily changed. The change in the damping constant is obtained by adjusting the distance between the conducting material which is the copper tube and the magnetic eld generator which is the magnet. In the rst design, which includes an inertial ampli cation mechanism, vertical motion is dampened by copper tube-ring magnet couple, which serves as a viscous damping component. For this design, a prototype is produced and experimental measurements are taken to show the e ect of damping on vibration amplitudes. In the second design, which includes local resonators, it is aimed to generate a vibration stop band at low frequencies. The e ect of ECD on stop band width, resonance peaks and anti-resonance depth on the frequency response results are observed. For comparison purposes, frequency response of this design is obtained analytically, experimentally and numerically. By both of these designs, it is shown that ECD can be used in di erent structures to attenuate vibrations.
Keywords: Eddy currents (Electric)